HUBUNGAN PENGETAHUAN IBU TERHADAP KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS ABANG I - Juniantari, Ni Putu Manik; Komang Yogi Triana; Ni Made Ari Sukmandari; Ni Komang Purwaningsih (JURNAL KEPERAWATAN, 2024)
Background: Stunting is a condition in which children under the age of five fail to thrive due to a prolonged lack of nutrients. The mother's lack of information will influence her behavior in delivering adequate diet to her children. Aim: The purpose of this study was to investigate the correlation between mother's knowledge and stunting incidents experienced by toddlers in the working area of ​​Abang I Public Health Centre. Methodology: This study included a quantitative method, analytic observational research, and a cross-sectional strategy. 107 respondents were sampled using a purposive sampling procedure. The analyzed using the Spearman Rank test. Result: The study results revealed that p-value = 0.001 = 0.05, indicating that H0 was rejected and Ha was accepted. Conclusions: There was a correlation between mother's knowledge and stunting incidents experienced by toddlers in the working area of ​​Abang I Public Health Centre.   Keywords: Mother’s knowledge; Stunting; Toddlers.